Factors that affect selection of elite women's sculling crews - Lawton, T. W.; Cronin, J. B.; McGuigan, M. R. (International Journal of Sports Physiology and Performance, 2013)
Purpose: There is no common theory on criteria to appropriately select crew rowers in pursuit of small performance gains. The purpose of this study was to establish whether anthropometry, rowing ergometry, or lower body strength were suitable criteria to identify differences between selected and nonselected sculling crews. Method: Twelve elite women performed a 2000-m ergometer time trial and a 5-repetition leg-press dynamometer test, were anthropometrically profiled, and participated in on-water national crew seat-racing trials. Log-transformed data were analyzed to compare percent (± SD) and standardized differences in group means (ES; ± 90% confidence interval [CI]) between selected and nonselected oarswomen, with adjustments for body mass where appropriate. Results: Selected crew boats were 4.60% ± 0.02% faster and won by an average margin of 13.5 ± 0.7 s over 1500 m. There were no differences between crews on average in height, arm span, seated height, body mass, or 8-site skinfold sum (body fat). Difference in 2000-m ergometer times were also trivial (ES = 0.2, 90%CI = -0.6 to 1.1, P = .63); however, selected crews had moderately greater leg-press strength (ES = 1.1, 90%CI = 0.3-1.9, P = .03). Conclusion: Selected oarswomen with comparable anthropometry and 2000-m ergometer ability had greater lower body strength. Coaches of elite oarswomen might consider leg strength as part of crew-selection criteria, given acceptable on-water boatmanship and attainment of 2000-m ergometer benchmarks.